Brief Intervention for Daily Marijuana Users Identified by Screening in Primary Care: A Subgroup Analysis of the Aspire Randomized Clinical Trial. Issue 2 (April 2016) - Fuster, Daniel; Cheng, Debbie M.; Wang, Na; Bernstein, Judith A.; Palfai, Tibor P.; Alford, Daniel P.; Samet, Jeffrey H.; Saitz, Richard
Background: The use of brief intervention for decreasing frequent marijuana use holds potential, but its efficacy in primary care is not known. Methods: Objective: To assess the impact of 2 brief interventions on marijuana use among daily/or almost daily marijuana users. Design: Subgroup analysis of a 3-arm randomized clinical trial of 2 brief counseling interventions compared with no brief intervention on daily marijuana use in a primary care setting (ASPIRE). Participants: ASPIRE study participants who both reported 21–30 days of marijuana use during the past month and identified marijuana as their drug of most concern. Interventions: (1) brief negotiated interview (BNI), a 10–15-minute structured interview, and (2) an adaptation of motivational interviewing (MOTIV), a 30–45-minute intervention. Control group participants received only a list of substance use treatment resources. Main measures: The primary outcome was number of days of marijuana use in the past 30 days at the 6-month follow-up. Secondary outcomes were (1) number of days of marijuana use at 6-week follow-up and (2) drug problems (Short Inventory of Problems—Drugs, SIP-D) at 6-week and 6-month follow-ups. Differences between intervention groups were analyzed using negative binomial regression models. Results: Among the 167 eligible participants, we did not find any significant impact of either of the 2 interventions on past 30 days of marijuana use at 6 months (adjusted incidence rate ratio [aIRR]: 0.95, 95% confidence interval [CI]: 0.75–1.15, P = .82 for BNI vs. control; aIRR: 1.02, 95% CI: 0.85–1.23, P = .82 for MOTIV vs. control). There was no significant impact on drug-related problems at 6-month follow-up (aIRR: 1.12, 95% CI: 0.69–1.82, P = .66 and aIRR: 1.46, 95% CI: 0.89–2.38, P = .27 for BNI vs. control and MOTIV vs. control, respectively). Results were similar at 6 weeks. Conclusions: Brief intervention has no apparent impact on marijuana use or drug-related problems among primary care patients with frequent marijuana use identified by screening.